Brentuximab Vedotin in Transplant-Naïve Relapsed/Refractory Hodgkin Lymphoma: Experience in 30 Patients. (23rd October 2015) - Zinzani, Pier Luigi; Pellegrini, Cinzia; Cantonetti, Maria; Re, Alessandro; Pinto, Antonello; Pavone, Vincenzo; Rigacci, Luigi; Celli, Melania; Broccoli, Alessandro; Argnani, Lisa; Pulsoni, Alessandro
Abstract: Background: Hodgkin lymphoma (HL) is characterized by the presence of CD30-positive Hodgkin Reed-Sternberg cells. Approximately 30%–40% of patients with advanced disease are refractory to frontline therapy or will relapse after first-line treatment. The standard management of these patients is salvage chemotherapy followed by high-dose chemotherapy and autologous stem cell transplant (ASCT). The best prognostic factor is the status of disease before ASCT; in particular, the normalization of positron emission tomography (PET) scan. Brentuximab vedotin (BV) has shown a high overall response rate in refractory/relapsed HL after ASCT, whereas few data are available regarding its role before ASCT. Patients and Methods: A multicenter, retrospective, observational study was conducted. The primary endpoint of the study was the effectiveness of BV as single agent in patients with relapsed/refractory, ASCT-naïve HL, determined by the conversion of PET status from positive to negative; secondary endpoints were safety, capacity to proceed to ASCT, survival, and progression-free status. Results: Thirty patients with relapsed/refractory HL- and PET-positive disease after conventional chemotherapy salvage treatments were treated with a median of 4 cycles of BV. Normalization of PET findings (Deauville score ≤2) occurred in 9 of 30 patients (30%). Those nine patients proceeded to ASCT. Conclusion: These data suggest that BV can normalize PET status in a subset of HL patients refractory to conventional chemotherapy salvage treatments, such as ifosfamide-containing regimens, cytarabine- and platinum-containing regimens, prior to ASCT. Abstract : This study evaluated the effectiveness of brentuximab vedotin (BV) in 30 autologous stem cell transplantation (ASCT)-naïve patients with relapsed/refractory Hodgkin lymphoma and positron emission tomography-positive (PET) disease after conventional chemotherapy salvage treatments. The primary endpoint was the conversion of PET-positive to PET-negative status after four cycles of BV. PET normalization occurred in nine patients; these patients subsequently received ASCT.